A first look at phototransferred thermoluminescence of rose quartz - Ferreira, I. A.; Nunes, M. C.S. [UNESP]; Yoshimura, E. M.; Trindade, N. M.; Chithambo, M. L. (Elsevier, 2024)
We report a preliminary study of phototransferred thermoluminescence (PTTL) induced by 470 nm light source in rose quartz. The glow curve corresponding to 1 Gy consists of five peaks at 76, 115, 180, 290 and 423 °C labelled I through V in that order. In the PTTL experiments employing blue light. PTTL was regenerated at peak I following preheating to remove peak I only and at peaks I and II otherwise. The dependence of the PTTL intensity on duration of illumination is analyzed in terms of a system of one acceptor and two donors in both cases. The mechanisms for the PTTL phenomena in the rose quartz are comprehensively discussed in this paper.
Keywords: Dosimetry; Phototransferred thermoluminescence; Rose quartz